Solid electrolyte tube with wide temperature range and high ionic conductivity as well as preparation method and application of solid electrolyte tube

By using sulfide solid electrolyte and isostatic pressure treatment processes, a solid electrolyte tube with wide temperature and high ionic conductivity was prepared, and an interface protective layer was introduced on the negative electrode side, which solved the low conductivity and cost of traditional oxide electrolyte tubes at room temperature. High-quality problems achieve efficient and safe energy storage technology.

CN119419338AInactive Publication Date: 2025-02-11LIYANG ZHONGKE GUNENG NEW ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510014741.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional oxide electrolyte tubes have low conductivity, high preparation cost, high maintenance cost and safety hazards at room temperature, and cannot meet the energy storage needs of high power and fast reactions.

Method used

Using sulfide as the solid electrolyte, a solid electrolyte tube with wide temperature and high ionic conductivity was prepared by isostatic treatment and ceramic sintering process, and an interface protective layer was introduced on the negative electrode side to reduce side reactions.

Benefits of technology

It achieves high ionic conductivity and excellent mechanical properties under normal temperature conditions, reduces the battery operating temperature, improves cycle stability and safety, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419338A_ABST
    Figure CN119419338A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of battery materials, and particularly relates to a wide-temperature high-ionic-conductivity solid electrolyte tube and a preparation method and application thereof. The wide-temperature high-ionic-conductivity solid electrolyte tube comprises a main body and an interface protection layer, the interface protection layer is arranged on the outer side wall of the main body; and the main body is formed by performing ceramic processing and curing on dielectric powder through compaction treatment and / or sintering treatment. According to the present invention, the working temperature of the sulfide electrolyte tube cylindrical battery can be significantly reduced in cooperation with the liquid lithium metal negative electrode, such that the sulfide electrolyte tube cylindrical battery can efficiently operate in the room temperature range, and the good electrochemical performance can be represented in the wide temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to a solid electrolyte tube with wide temperature range and high ion conductivity, and a preparation method and application thereof. Background Art

[0002] As a new type of energy storage device, the electrolyte tube cylindrical battery has received widespread attention. Although traditional liquid batteries have excellent performance in energy density, they are insufficient in safety and reliability. Liquid electrolytes are prone to leakage and cause fire risks. Therefore, solid-state battery technology has gradually become the focus of research. Solid-state batteries overcome the safety hazards of liquid electrolytes by using solid electrolytes, while providing better structural stability.

[0003] Sulfide solid electrolytes have become key materials for improving battery performance due to their high ionic conductivity and excellent mechanical properties. Electrolyte tube cylindrical batteries combine the advantages of solid electrolytes, enabling fast ion conduction and long-term cycle stability, and are particularly suitable for high-safety and high-performance application scenarios. With the increasing demand for electric vehicles and renewable energy storage, electrolyte tube cylindrical batteries are expected to play an important role in the future market and promote the development of efficient and safe energy storage technologies. In the existing technical solutions, there are still technical defects in the use of oxide electrolytes. For example, the conductivity of oxide electrolytes at room temperature is as low as 10 -3 ~10 -4 S cm -1 The prepared batteries cannot meet the requirements of high power and rapid response in the field of energy storage; the preparation of oxide electrolyte tubes requires sintering at above 1700°C, which leads to high process cost, low efficiency and more time consumption; increasing the electronic conductivity of the oxide solid electrolyte and heating the lithium negative electrode to a molten state at the same time causes the operating temperature of the oxide battery to rise to more than 240°C, resulting in high maintenance costs for the battery and obvious safety hazards.

[0004] Sulfide solid electrolyte has excellent ion transport performance, and its ion conductivity is comparable to that of liquid electrolyte. 2− The large radius and strong electric field can easily deform the cation electron cloud, which is conducive to building a wider and more efficient lithium ion transport pathway. On the other hand, the sulfur atom has a small electronegativity and a small interaction force with adjacent skeleton ions, which is conducive to increasing the concentration of free lithium ions. In addition, sulfide solid electrolytes are relatively soft, and most sulfide solid electrolytes can be tightly connected by simple cold pressing to show high cold pressed ion conductivity, which is unmatched by oxide electrolytes. Summary of the invention

[0005] The technical solution of the present invention aims to solve the technical problems of traditional electrolyte tubes, such as low room temperature conductivity, high operating temperature, high preparation cost and high maintenance cost, and provides a wide temperature range and high ionic conductivity solid electrolyte tube and its preparation method and application.

[0006] The main purposes of the present invention are: 1. To introduce a new type of electrolyte tube with wide temperature range and high ionic conductivity.

[0007] 2. Improve battery safety and application possibilities.

[0008] To achieve the above objectives, the present invention adopts the following technical solutions.

[0009] A wide temperature range high ion conductivity solid electrolyte tube, comprising a main body and an interface protection layer; the interface protection layer is arranged on the outer side wall of the main body.

[0010] A method for preparing a wide-temperature, high-ion-conductivity solid electrolyte tube, the method comprising: (1) adding dielectric powder as a raw material into a mold and applying pressure to form a U-shaped solid electrolyte tube primary product.

[0011] (2) Sintering the initial U-shaped solid electrolyte tube to produce an initial optimized solid electrolyte tube.

[0012] (3) The negative electrode side of the optimized sulfide solid electrolyte tube is subjected to interface protection to form a solid electrolyte tube.

[0013] Preferably, the dielectric powder in step (1) is a sulfide solid electrolyte.

[0014] The step (1) of adding the dielectric powder to the rubber mold and applying pressure thereto is to add the dielectric powder to the rubber mold, and after roller compaction, perform isostatic pressing on the mold at a pressure of 540 to 560 kN for 45 to 75 seconds.

[0015] Preferably, after the dielectric powder is added into the rubber mold, the positive electrode current collector rod is inserted.

[0016] Preferably, the sintering in step (2) is to sinter the U-shaped solid electrolyte tube in sections.

[0017] The staged sintering comprises: firstly keeping the temperature at 290-310°C for 20-30 minutes, then heating to 470-490°C at a heating rate of 1°C / min, and keeping the temperature at this temperature for 4-8 hours.

[0018] Preferably, the interface in step (3) is prepared by uniformly mixing lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile to prepare a LiTFSI / PEO / ACN solution, which is evenly applied on the outer wall of the U-shaped tube and placed on a heating table for rapid heating to remove the ACN solution.

[0019] Preferably, the mass ratio of the lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile is 1:(4.2-4.6):(14.1-14.5).

[0020] An application of a wide-temperature high-ion conductivity solid electrolyte tube, wherein the solid electrolyte tube is used for constructing a wide-temperature electrochemical system.

[0021] Preferably, the wide temperature electrochemical system comprises a lithium-sulfur battery.

[0022] In the technical solution of the present invention, the core lies in using sulfide as a solid electrolyte to reduce the side reactions between the liquid lithium metal negative electrode and the sulfide electrolyte tube, and improve the cycle stability of the sulfide solid lithium metal battery. Under normal temperature conditions, this type of electrolyte exhibits excellent ionic conductivity and excellent mechanical properties. By adopting particle refinement technology and isostatic pressing process, it was successfully prepared into a cylindrical electrolyte tube. Subsequently, the electrolyte tube undergoes a fine ceramic sintering process to reduce grain boundaries and enhance its density, thereby increasing the critical current density. In addition, this technical solution innovatively introduces a protective film, the purpose of which is to effectively alleviate the side reactions that may occur between the liquid lithium metal negative electrode and the sulfide electrolyte tube. At the same time, an interface protective layer is formed by in-situ polymerization technology to strengthen the interface bonding between the positive electrode active material and the sulfide solid electrolyte tube to ensure a stable structure. The interface protective layer acts as a bridge between the interface of lithium metal and the sulfide electrolyte membrane, significantly enhancing the lithium ion transmission efficiency, and effectively blocking the direct contact between lithium metal and the electrolyte, thereby inhibiting the occurrence of potential side reactions between the two.

[0023] In the technical solution of the present invention, another core point is to reduce the internal structural gaps of the solid electrode by regulating the sintering temperature and sintering method. This technology can significantly improve the microstructure of the material, making it more compact. During the sintering process, the contact between the particles becomes closer, and the number of pores and cracks is significantly reduced. Through heat treatment, the lattice defects in the crystal can be significantly reduced, promoting the improvement of the crystal structure, thereby improving the carrier migration efficiency and overall electrical performance.

[0024] Specifically, when the sintering temperature is set to 300 °C, the surface of the material begins to show a trend of densification, but cracks and holes still exist. As the sintering temperature increases to 400 °C, the surface density is further enhanced, the corresponding number of cracks and holes is significantly reduced, and the ionic conductivity is also increased accordingly. When the sintering temperature continues to increase to 490 °C, the surface of the material reaches the optimal density state, the cracks and holes almost disappear, and the ionic conductivity reaches a peak. However, if the sintering temperature is further increased, cracks will appear on the secondary sintering surface again, which is due to the stress and strain caused by the decomposition of the electrolyte caused by excessive temperature. The pores formed by these decomposition products will reduce the ionic conductivity of the solid electrolyte.

[0025] The advantages of the present invention are: with the use of liquid lithium metal anode (Li-Phen-Ether), the operating temperature of sulfide electrolyte cylindrical battery is significantly reduced, so that it can operate efficiently within the room temperature range and can also show good electrochemical performance in a wider temperature range. This technological breakthrough has opened up new paths and broad market opportunities for the practical application of sulfide solid-state batteries, and also provided strong support for solving the defects of high cost, low efficiency and long time consumption in current technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Comparison of the microscopic morphology of the cross section of the electrolyte tube before and after sintering.

[0027] Figure 2 Comparison of the microscopic morphology of the electrolyte tube surface before and after sintering.

[0028] Figure 3 The critical current density of the sulfide solid electrolyte tubular symmetrical battery prepared by the operating process of Example 2 is measured and characterized.

[0029] Figure 4 The critical current density of the sulfide solid electrolyte tubular symmetrical battery prepared by the operating process of Comparative Example 1 is measured and characterized.

[0030] Figure 5 For Example 2 and Comparative Example 1 at 1.0 mA / cm 2 Characterization results of long-term cycling of symmetric batteries at current density and 0.27 V.

[0031] Figure 6 The time-voltage curve of comparative example 3 obtained by cycle testing at a temperature of 55°C is shown in FIG.

[0032] Figure 7 This is a characterization result diagram of the specific capacity and coulombic efficiency of the variable rate charge and discharge cycle battery at 20°C.

[0033] Figure 8 This is a characterization result diagram of the specific capacity and coulombic efficiency of the variable rate charge and discharge cycle battery at 30°C.

[0034] Fig. 9 This is a characterization result diagram of the specific capacity and coulombic efficiency of the variable rate charge and discharge cycle battery at 40°C.

[0035] Fig.10 This is a characterization result diagram of the specific capacity and coulombic efficiency of the variable rate charge and discharge cycle battery at 55°C.

[0036] Fig.11 This is a characterization diagram of the exchange current density of the symmetrical battery of the sample prepared in Example 2 at different temperatures.

[0037] Fig.12 The impedance characterization diagram of the symmetrical battery of the sample prepared in Example 2 at different temperatures.

[0038] Fig.13 This is the SEM characterization image of the solid electrolyte tube surface after the protective layer is formed.

[0039] Fig.14 This is the EDS characterization image of the solid electrolyte tube surface after the protective layer is formed. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0041] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0042] Embodiment 1: A wide-temperature high-ionic conductivity solid electrolyte tube, the wide-temperature high-ionic conductivity solid electrolyte tube comprising a main body and an interface protection layer.

[0043] The interface protection layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide and is arranged on the negative electrode side of the outer wall of the main body.

[0044] The main body is formed by ceramicizing and solidifying LPSCl solid electrolyte powder through compaction and sintering.

[0045] The wide temperature range and high ionic conductivity solid electrolyte tube is prepared by the following method: (1) Weigh an appropriate amount of LPSCl solid electrolyte powder, pour it into a rubber mold, and then insert the positive electrode current collector rod; to ensure that the thickness of the electrolyte tube obtained after isostatic pressing is uniform, roll the mold with the positive electrode current collector rod inserted back and forth on the platform for 5 times to make the solid electrolyte powder evenly distributed in the mold; put the mold into a plastic bag, evacuate it, and transfer it from the glove box to the cavity of the isostatic pressing equipment; immerse the plastic bag completely in hydraulic oil, start the isostatic pressing equipment, and slowly pressurize it. When the pressure reaches 550 kN, stop pressurizing, maintain the pressure for 1 min, and then take it out; after taking it out, wipe the hydraulic oil on the surface of the plastic bag clean, transfer it to the glove box, and then disassemble the mold to make a U-shaped solid electrolyte tube. After isostatic pressing, take samples and perform SEM characterization on them. The characterization results are as follows: Figure 1 and Figure 2 As shown, it can be seen that a relatively dense structure can be formed by isostatic pressing.

[0046] (2) The U-shaped tube was sealed into a cylindrical ceramic boat and kept at 290 °C in a muffle furnace for 30 min. The temperature was then increased to 470 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. SEM characterization was also performed before and after the secondary sintering. The characterization results are shown in Figure 2. Figure 1 and Figure 2 As shown, it can be seen that a large number of structural defects are eliminated through effective secondary sintering.

[0047] (3) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile were mixed evenly in a mass ratio of 1:4.2:14.1 to prepare a LiTFSI / PEO / ACN solution. The solution was evenly applied to the outer wall of the U-shaped tube and quickly heated on a heating table at 100 °C to remove the ACN solution. Interface protection was performed on the negative electrode side. After the protective layer was formed, SEM and EDS characterization were performed. The SEM characterization results are shown in FIG. Fig.13 As shown, the EDS characterization results are as follows Fig.14 As shown, a solid electrolyte tube is made.

[0048] The solid electrolyte tube prepared in the example was placed in a 18650 cylindrical battery case, the positive electrode current collector was connected to the positive electrode of the battery case, and then a liquid lithium metal negative electrode solution was added, and the battery was sealed with organic silica gel to prepare a battery. The battery was tested for performance, and the specific characterization results are as follows.

[0049] Rate performance test: The electrolyte tube prepared in the example was made into a battery, and 25 charge and discharge cycles were performed at 0.3 C at temperatures of 20°C, 30°C, 40°C and 55°C, respectively, to test the specific capacity and coulombic efficiency of the battery. The specific characterization results are as follows.

[0050]

[0051] In addition, at 20 ℃, 30 ℃, 40 ℃ and 55 ℃, variable rate charge and discharge cycles were carried out at 0.3 C and / or 0.5 C and / or 0.8 C and / or 1.0 C rates, respectively, to detect the specific capacity and coulombic efficiency of the battery. The specific characterization results are as follows: Figures 7 to 11 As shown. Figures 7 to 11 It can be seen that when it works at 40-55 ℃, increasing the cycle rate will not cause an irreversible decrease in the specific capacity and coulombic efficiency of the battery. When it is restored to a low rate state after several cycles at a high rate, the specific capacity and coulombic efficiency can be efficiently restored, and excellent performance can be maintained even at 30 ℃. However, the liquid lithium cylindrical battery constructed with a commercially available oxide solid electrolyte tube (i.e., the same type of comparison battery) cannot work effectively at 30 ℃, and its specific capacity is almost 0 mAh / g, and its coulombic efficiency is almost 0%.

[0052] Battery long cycle test: The electrolyte tube prepared in the example was made into a battery, and 10 charge and discharge long cycles were performed at 0.3 C at temperatures of 20°C, 30°C, 40°C and 55°C, respectively, to test the specific capacity of the battery. The specific characterization results are as follows.

[0053]

[0054] Cycle life test evaluation: Under the environmental conditions of 20 ℃ and 40 ℃, the battery was charged at 0.2 C current and discharged at 0.55 C current, and a total of 100 charging cycles were tested. The specific characterization results are as follows.

[0055]

[0056] Embodiment 2: A wide-temperature high-ionic conductivity solid electrolyte tube, the wide-temperature high-ionic conductivity solid electrolyte tube comprising a main body and an interface protection layer.

[0057] The interface protection layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide and is arranged on the negative electrode side of the outer wall of the main body.

[0058] The main body is formed by ceramicizing and solidifying LPSCl solid electrolyte powder through compaction and sintering.

[0059] The wide temperature range and high ionic conductivity solid electrolyte tube is prepared by the method: (1) weighing an appropriate amount of LPSCl solid electrolyte powder, pouring it into a rubber mold, and then inserting a positive electrode current collector rod; to ensure that the thickness of the electrolyte tube obtained after isostatic pressing is uniform, the mold with the positive electrode current collector rod inserted is rolled back and forth on a platform for 8 times so that the solid electrolyte powder is evenly distributed in the mold; the mold is placed in a plastic bag, evacuated, and transferred from a glove box to a cavity of an isostatic pressing device; the plastic bag is completely immersed in hydraulic oil, the isostatic pressing device is started, and the pressure is slowly increased. When the pressure reaches 550 kN, the pressure is stopped, and the pressure is maintained for 1 min before being taken out; after taking out, the hydraulic oil on the surface of the plastic bag is wiped clean, and the bag is transferred to a glove box and the mold is disassembled to obtain a U-shaped solid electrolyte tube.

[0060] (2) The U-shaped tube was sealed into a cylindrical ceramic boat and kept at 300 °C in a muffle furnace for 25 min. The temperature was then increased to 480 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h.

[0061] (3) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile were mixed evenly in a mass ratio of 1:4.4:14.3 to prepare a LiTFSI / PEO / ACN solution. The solution was evenly applied to the outer wall of the U-shaped tube and quickly heated on a heating table at 100 °C to remove the ACN solution. The interface was protected on the negative electrode side to prepare a solid electrolyte tube.

[0062] The solid electrolyte tube prepared in the example was placed in a 18650 cylindrical battery case, the positive electrode current collector was connected to the positive electrode of the battery case, and then a liquid lithium metal negative electrode solution was added, and the battery was sealed with organic silica gel. The battery was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.

[0063]

[0064]

[0065] In addition, cycle life test evaluation is also carried out, and the characterization results are as follows.

[0066]

[0067] In addition, the exchange current density and impedance of the symmetrical battery of the samples prepared in this example at different temperatures were characterized. The characterization results are shown in Fig.11 and Fig.12 It shows better performance under different temperature conditions.

[0068] Embodiment 3: A wide-temperature high-ionic conductivity solid electrolyte tube, the wide-temperature high-ionic conductivity solid electrolyte tube comprising a main body and an interface protection layer.

[0069] The interface protection layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide and is arranged on the negative electrode side of the outer wall of the main body.

[0070] The main body is formed by ceramicizing and solidifying LPSCl solid electrolyte powder through compaction and sintering.

[0071] The wide temperature range and high ionic conductivity solid electrolyte tube is prepared by the method: (1) weighing an appropriate amount of LPSCl solid electrolyte powder, pouring it into a rubber mold, and then inserting a positive electrode current collector rod; to ensure that the thickness of the electrolyte tube obtained after isostatic pressing is uniform, the mold with the positive electrode current collector rod inserted is rolled back and forth on a platform for 10 times so that the solid electrolyte powder is evenly distributed in the mold; the mold is placed in a plastic bag, evacuated, and transferred from a glove box to a cavity of an isostatic pressing device; the plastic bag is completely immersed in hydraulic oil, the isostatic pressing device is started, and the pressure is slowly increased. When the pressure reaches 550 kN, the pressure is stopped, and the pressure is maintained for 1 min before being taken out; after taking out, the hydraulic oil on the surface of the plastic bag is wiped clean, and the bag is transferred to a glove box and the mold is disassembled to obtain a U-shaped solid electrolyte tube.

[0072] (2) The U-shaped tube was sealed into a cylindrical ceramic boat and kept at 310 °C in a muffle furnace for 20 min. The temperature was then increased to 490 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h.

[0073] (3) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile were mixed evenly in a mass ratio of 1:4.6:14.5 to prepare a LiTFSI / PEO / ACN solution. The solution was evenly applied to the outer wall of the U-shaped tube and quickly heated on a heating table at 100 °C to remove the ACN solution. The interface was protected on the negative electrode side to prepare a solid electrolyte tube.

[0074] The solid electrolyte tube prepared in the example was placed in a 18650 cylindrical battery case, the positive electrode current collector was connected to the positive electrode of the battery case, and then a liquid lithium metal negative electrode solution was added, and the battery was sealed with organic silica gel. The battery was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.

[0075]

[0076]

[0077] In addition, cycle life test evaluation is also carried out, and the characterization results are as follows.

[0078]

[0079] Comparative Example 1: A method for preparing a solid electrolyte tube, the specific preparation method is the same as Example 2, except that the secondary sintering process unique to the present invention is not used to prepare the solid electrolyte tube, and the specific operation is as follows: A wide temperature and high ionic conductivity solid electrolyte tube, the wide temperature and high ionic conductivity solid electrolyte tube includes a main body and an interface protective layer; the interface protective layer is composed of lithium bistrifluoromethanesulfonyl imide and polyethylene oxide, and is arranged on the negative electrode side of the outer wall of the main body; the main body is formed by ceramic processing and solidification of LPSCl solid electrolyte powder through compaction and sintering.

[0080] The wide temperature range and high ionic conductivity solid electrolyte tube is prepared by the method: (1) weighing an appropriate amount of LPSCl solid electrolyte powder, pouring it into a rubber mold, and then inserting a positive electrode current collector rod; to ensure that the thickness of the electrolyte tube obtained after isostatic pressing is uniform, the mold with the positive electrode current collector rod inserted is rolled back and forth on a platform for 8 times so that the solid electrolyte powder is evenly distributed in the mold; the mold is placed in a plastic bag, evacuated, and transferred from a glove box to a cavity of an isostatic pressing device; the plastic bag is completely immersed in hydraulic oil, the isostatic pressing device is started, and the pressure is slowly increased. When the pressure reaches 550 kN, the pressure is stopped, and the pressure is maintained for 1 min before being taken out; after taking out, the hydraulic oil on the surface of the plastic bag is wiped clean, and the bag is transferred to a glove box and the mold is disassembled to obtain a U-shaped solid electrolyte tube.

[0081] (2) The U-shaped tube was sealed into a cylindrical ceramic boat and kept at 300 °C in a muffle furnace for 6 h.

[0082] (3) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile were mixed evenly in a mass ratio of 1:4.4:14.3 to prepare a LiTFSI / PEO / ACN solution. The solution was evenly applied to the outer wall of the U-shaped tube and quickly heated on a heating table at 100 °C to remove the ACN solution. The interface was protected on the negative electrode side to prepare a solid electrolyte tube.

[0083] The solid electrolyte tube prepared in the comparative example was placed in a 18650 cylindrical battery case, the positive electrode current collector was connected to the positive electrode of the battery case, and then a liquid lithium metal negative electrode solution was added, and the battery was sealed with organic silica gel to prepare a battery. The battery critical current density was tested for the batteries prepared in Examples 1 to 3 and this example, and the characterization results of Example 2 and this example are shown in FIG. Figure 3 and Figure 4 .

[0084] analyze Figure 3 and Figure 4The characterization data of the battery showed that the critical current density of the secondary sintered sulfide solid electrolyte tube was 4.07 mA / cm -2 Its performance is significantly better than that of the sulfide solid electrolyte tube without secondary sintering, with a critical current density of 3.06 mA / cm -2 By observing the microscopic morphology of the solid electrolyte tubes of Comparative Example 3 and Comparative Example 1, it can be clearly observed that the microscopic gaps are healed by secondary sintering, the number of grain boundaries inside the electrolyte tube is reduced, and the electrochemical stability is improved.

[0085] In addition, the battery prepared in Example 2 and the battery prepared in Comparative Example 1 were tested at 1.0 mA / cm 2 Symmetrical battery long cycle measurement was carried out under current density and 0.27 V conditions. The specific characterization results are as follows Figure 5 .

[0086] analyze Figure 5 According to the characterization data, the battery without secondary sintering failed after 266 h of cycling, while the cycle life of the symmetrical battery after secondary sintering was greatly extended to >550 h. Based on the above tests, the processing technology provided by the present invention has important application potential for realizing safer and more stable lithium batteries.

[0087] Comparative Example 2: A method for preparing a solid electrolyte tube. The specific preparation method is the same as Example 2, except that the temperature of the secondary sintering process unique to the present invention is changed to prepare the solid electrolyte tube. The specific operation is as follows: A wide temperature range, high ionic conductivity solid electrolyte tube, the wide temperature range, high ionic conductivity solid electrolyte tube comprising a main body and an interface protective layer; the interface protective layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide, and is arranged on the negative electrode side of the outer wall of the main body; the main body is formed by ceramic processing and solidification of LPSCl solid electrolyte powder through compaction and sintering.

[0088] The wide temperature range and high ionic conductivity solid electrolyte tube is prepared by the method: (1) weighing an appropriate amount of LPSCl solid electrolyte powder, pouring it into a rubber mold, and then inserting a positive electrode current collector rod; to ensure that the thickness of the electrolyte tube obtained after isostatic pressing is uniform, the mold with the positive electrode current collector rod inserted is rolled back and forth on a platform for 8 times so that the solid electrolyte powder is evenly distributed in the mold; the mold is placed in a plastic bag, evacuated, and transferred from a glove box to a cavity of an isostatic pressing device; the plastic bag is completely immersed in hydraulic oil, the isostatic pressing device is started, and the pressure is slowly increased. When the pressure reaches 550 kN, the pressure is stopped, and the pressure is maintained for 1 min before being taken out; after taking out, the hydraulic oil on the surface of the plastic bag is wiped clean, and the bag is transferred to a glove box and the mold is disassembled to obtain a U-shaped solid electrolyte tube.

[0089] (2) The U-shaped tube was sealed into a cylindrical ceramic boat and kept at 300 °C in a muffle furnace for 25 min. The temperature was then increased to 500 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h.

[0090] (3) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile were mixed evenly in a mass ratio of 1:4.4:14.3 to prepare a LiTFSI / PEO / ACN solution. The solution was evenly applied to the outer wall of the U-shaped tube and quickly heated on a heating table at 100 °C to remove the ACN solution. The interface was protected on the negative electrode side to prepare a solid electrolyte tube.

[0091] The solid electrolyte tube prepared in the comparative example was placed in a 18650 cylindrical battery case, the positive electrode current collector was connected to the positive electrode of the battery case, and then a liquid lithium metal negative electrode solution was added, and the battery was sealed with organic silica gel. The battery was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.

[0092]

[0093]

[0094] In addition, cycle life test evaluation is also carried out, and the characterization results are as follows.

[0095]

[0096] Analyzing the above characterization results, the battery prepared in Comparative Example 2 is subjected to secondary sintering at a relatively high temperature, and the sulfide solid electrolyte undergoes thermal decomposition during the sintering process, wherein the other and other unstable compounds produced will destroy the structural integrity of the electrolyte, reduce the battery ion conductivity, and cause the battery performance to decrease. In addition, the unstable sulfide compounds and electrode materials will undergo thermochemical reactions, especially in very low temperature environments without direct contact. Such side reactions may cause combustion or explosion, posing serious safety hazards to the battery. After further research and observation, it is found that excessively high secondary sintering temperatures will lead to the generation of new defects, especially near the grain boundaries, which will lead to an increase in grain boundary defects, thereby reducing the conductivity of the material. At the same time, the substantial decrease in the effective contact area significantly increases the interface impedance, hindering the transmission of lithium ions.

[0097] Comparative Example 3: A method for preparing a solid electrolyte tube. The specific preparation method is the same as Example 2, except that the temperature of the secondary sintering process unique to the present invention is changed to prepare the solid electrolyte tube. The specific operations are as follows: A wide temperature range, high ionic conductivity solid electrolyte tube, the wide temperature range, high ionic conductivity solid electrolyte tube comprising a main body and an interface protective layer; the interface protective layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide, and is arranged on the negative electrode side of the outer wall of the main body; the main body is formed by ceramic processing and solidification of LPSCl solid electrolyte powder through compaction and sintering.

[0098] The wide temperature range and high ionic conductivity solid electrolyte tube is prepared by the method: (1) weighing an appropriate amount of LPSCl solid electrolyte powder, pouring it into a rubber mold, and then inserting a positive electrode current collector rod; to ensure that the thickness of the electrolyte tube obtained after isostatic pressing is uniform, the mold with the positive electrode current collector rod inserted is rolled back and forth on a platform for 8 times so that the solid electrolyte powder is evenly distributed in the mold; the mold is placed in a plastic bag, evacuated, and transferred from a glove box to a cavity of an isostatic pressing device; the plastic bag is completely immersed in hydraulic oil, the isostatic pressing device is started, and the pressure is slowly increased. When the pressure reaches 550 kN, the pressure is stopped, and the pressure is maintained for 1 min before being taken out; after taking out, the hydraulic oil on the surface of the plastic bag is wiped clean, and the bag is transferred to a glove box and the mold is disassembled to obtain a U-shaped solid electrolyte tube.

[0099] (2) The U-shaped tube was sealed into a cylindrical ceramic boat and kept at 300 °C in a muffle furnace for 25 min. The temperature was then increased to 320 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h.

[0100] (3) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile were mixed evenly in a mass ratio of 1:4.4:14.3 to prepare a LiTFSI / PEO / ACN solution. The solution was evenly applied to the outer wall of the U-shaped tube and quickly heated on a heating table at 100 °C to remove the ACN solution. The interface was protected on the negative electrode side to prepare a solid electrolyte tube.

[0101] The solid electrolyte tube prepared in the comparative example was placed in a 18650 cylindrical battery case, the positive electrode current collector was connected to the positive electrode of the battery case, and then a liquid lithium metal negative electrode solution was added, and the battery was sealed with organic silica gel. The battery was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.

[0102]

[0103]

[0104] In addition, the battery was cycled at 55 °C and the time-voltage curve was plotted. The characterization results are as follows: Figure 6 .

[0105] Analyzing the above characterization results, although the preparation method provided in Comparative Example 3 also uses a secondary sintering process, the secondary sintering temperature is not high, resulting in an unobvious thermal repair effect, and lithium dendrite tips will be generated on the surface of the solid electrolyte. In view of the non-uniformity of the lithium deposition process, a local pressure increase occurs in the contact point area. With the continuous filling of lithium metal, the internal fracture of the grain induced by the current will gradually develop and expand. At the same time, the grain boundary of the solid electrolyte, as a weak link in the microstructure, its atomic structure and density changes make it extremely susceptible to the influence of lithium dendrites, becoming a potential defect area. In actual use, as the battery temperature increases, the diffusion coefficient of lithium ions in the electrolyte increases, which improves the ion mobility. At the same time, it also causes the growth rate of lithium dendrites to accelerate, resulting in uneven local hot spots inside the battery, triggering internal short circuits, especially in locations where there are many lithium dendrites. Lithium dendrites can penetrate the diaphragm (SEI) and cause the battery to short-circuit.

[0106] Comparative Example 4: A commercially available lithium-ion battery, which is a 18650 battery, was subjected to partial performance testing in the same manner as in Example 1, and the characterization results are as follows.

[0107]

[0108]

[0109] Analyzing the above characterization results, the key factors that cause the temperature of the battery to continue to rise in the thermal runaway process triggered by the lithium deposition side reaction in the commercial lithium-ion battery system can be summarized as follows: the first reason is the continuous proliferation of lithium dendrites on the surface of the negative electrode. These sharp dendrites eventually penetrate the solid electrolyte interface (SEI) diaphragm to form an internal short circuit, thereby causing the temperature to rise; secondly, the metal lithium deposited on the surface of the negative electrode and the "dead lithium" accumulated in the battery react violently with the electrolyte, and this process releases a large amount of heat energy; thirdly, when the battery encounters an overcharge condition, the high current density environment exacerbates the lithium deposition side reaction, which in turn causes the battery temperature to rise further; finally, as the temperature continues to rise, the electrolyte decomposes and releases gas, causing the internal pressure of the battery to increase sharply, causing the battery to deflate and the morphology of the metal lithium to change. At this stage, the moisture and oxygen in the air react violently with the exposed metal lithium, which may lead to serious consequences such as combustion, rapid volume expansion, and even explosion.

Claims

1. A wide temperature range and high ionic conductivity solid electrolyte tube, characterized in that: The wide temperature and high ion conductivity solid electrolyte tube comprises a main body and an interface protection layer; the interface protection layer is arranged on the outer side wall of the main body; the main body is composed of a sulfide solid electrolyte; the interface protection layer comprises lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide.

2. A method for preparing a wide temperature range high ionic conductivity solid electrolyte tube as claimed in claim 1, characterized in that: The method comprises: (1) adding dielectric powder as raw material into a mold and applying pressure to form a U-shaped solid electrolyte tube preliminary product; (2) sintering the U-shaped solid electrolyte tube preliminary product to form a preliminary optimized solid electrolyte tube; (3) performing interface protection on the negative electrode side of the preliminary optimized solid electrolyte tube to form a solid electrolyte tube.

3. The method for preparing a wide temperature range high ionic conductivity solid electrolyte tube according to claim 2, characterized in that: The dielectric powder in step (1) is a sulfide solid electrolyte; the adding to the mold and applying pressure in step (1) is to add the dielectric powder to the rubber mold, and after roller compaction, perform isostatic pressing on the mold at a pressure of 540 to 560 kN for 45 to 75 seconds.

4. The method for preparing a wide temperature range high ionic conductivity solid electrolyte tube according to claim 3, characterized in that: After the dielectric powder is added into the rubber mold, the positive electrode current collector rod is inserted.

5. The method for preparing a wide temperature range high ionic conductivity solid electrolyte tube according to claim 2, characterized in that: The sintering in step (2) is to perform segmented sintering on the U-shaped solid electrolyte tube; the segmented sintering comprises: firstly keeping the temperature at 290-310°C for 20-30 min, then heating the temperature to 470-490°C at a heating rate of 1°C / min, and keeping the temperature at this temperature for 4-8 h.

6. The method for preparing a wide temperature range high ionic conductivity solid electrolyte tube according to claim 2, characterized in that: The interface protection in step (3) is to mix lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile evenly to prepare a LiTFSI / PEO / ACN solution, evenly apply it on the outer wall of the U-shaped tube, and place it on a heating table and quickly heat it to remove the ACN solution.

7. The method for preparing a wide temperature range high ionic conductivity solid electrolyte tube according to claim 6, characterized in that: The lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and acetonitrile are in a mass ratio of 1:(4.2-4.6):(14.1-14.5).

8. An application of the wide temperature range high ion conductivity solid electrolyte tube as claimed in claim 1, characterized in that: The solid electrolyte tube is used for constructing a wide-temperature electrochemical system.

9. The use of a wide temperature range high ion conductivity solid electrolyte tube according to claim 8, characterized in that: The wide temperature electrochemical system includes a lithium-sulfur battery.

Citation Information

Patent Citations

  • Inorganic-organic nano composite solid electrolyte membrane and preparation method and application thereof

    CN109638349A

  • Lithium negative electrode protective film layer and preparation method thereof

    CN114068931A

  • Negative electrode sandwich structure as well as preparation method and application thereof

    CN114284507A

  • High-temperature melting lithium-iodine battery based on garnet solid electrolyte

    CN114335758A

  • Protective layer of cathode interface of sulfide solid-state lithium-sulfur battery, preparation method and battery

    CN115692714A